Interactive And Real-Time Dynamic Simulation Of A Heat Exchanger Using Python - Rajee, Tanusha Sharma (Universiti Sains Malaysia, 2021)
The current pandemic has rapidly changed the landscape engineering education as the need for social distancing has opened up unchartered areas such as the necessity for virtual laboratories, due to traditional laboratory practices not being a feasible option. However, the existing online lab modules still do not cover the extensive field of chemical engineering as it lacks in areas such as heat transfer and thermodynamics. In this study, a heat exchanger simulation is modelled with the use of the Python programming language, which is a free open-source software. The mathematical model implemented in this study to analyze the changes in the outlet temperature of the process streams was validated successfully, with a small deviation percentage of 0.69% and 0.33% for the hot and cold streams respectively, when compared with theoretical values obtained from literature. The Python Heat Exchanger Simulation was then developed, and its feasibility was tested by conducting studies based on the steady state, which had an error percentage of 0.71% and 0.33% as well as the dynamic behaviour, which had an error percentage of 1.3% and 1.1% for the hot and cold streams respectively, when compared with literature. The effect of manipulating process variables on the outlet temperature of both process streams were also performed, in the terms of sensitivity analysis to observe the simulation response to these changes. It was found that the inlet temperature of both streams had a significant effect on the transient temperature response of the heat exchanger simulation as compared to change in mass flowrate.